Limits of Application of the jura novit arbiter Principle in International Arbitration: Some Issues of Theory and Practice - D. L. Davydenko; R. N. Muksunova (Московский журнал международного права, 2023)
INTRODUCTION. The principle of jura novit arbiter or jura novit tribunus is an analogue of the doctrine of jura novit curia in international arbitration proceedings which is free from the peculiarities of national laws. The significance of its application in international arbitration lies in the powers of an arbitral tribunal to participate in ascertaining the content of the applicable law. Given the features of international arbitration, material limitations are put on the jura novit arbiter principle in order to protect the rights and interests of disputing parties. However, limitations have both positive and negative legal effects.MATERIALS AND METHODS. The authors researched the provisions of international treaties, case law of tribunals and state courts demonstrating the scope of the arbitrator’s discretionary powers and the effects of its limitation, as well as the works of Russian and foreign scholars. The methodological basis of the research includes general scientific and special methods.RESEARCH RESULTS. The analyses of international treaties and case law led to the elaboration of the list of the main limits of the jura novit arbiter application. The study examined the issues in the relationship between jura novit arbiter and other principles aimed at narrowing the scope of its functioning.DISCUSSION AND CONCLUSIONS. The results of the analysis allow to draw the following conclusions. First, there are three major constraints put on the arbitrators' discretion: 1) ne ultra petita (not beyond the request), 2) due process in terms of a right to be heard and the foreseeability test, 3) expediency and efficiency of arbitral proceedings. Secondly, the limitation of the principle is a double-edged sword: on the one hand, it ensures legal certainty and predictability of an arbitral proceeding and its outcome, secures the rights and interests of the parties. On the other hand, the aforementioned limitations reveal also some downsides: there is no clear guidance on identifying conditions under which the ne ultra petita principle does not serve as a boundary of the jura novit arbiter principle; the "foreseeability" is an evaluative concept; and the imbalance between expediency and efficiency principles and jura novit arbiter may give rise to concerns about the established content of the applicable law.